Whole-Body MRI Is an Effective Imaging Modality for Hematological Malignancy Treatment Response Assessment: A Systematic Review and Meta-Analysis - Lin, Guisen; Zong, Xiaodan; Li, Yaowen; Tan, Weiting; Sun, Weisheng; Zhang, Siqi; Gan, Yungen; Zeng, Hongwu (Frontiers in Oncology, 2022)
Objectives To evaluate the diagnostic accuracy of whole-body MRI (WB-MRI) for assessment of hematological malignancies’ therapeutic response. Methods PubMed, Embase, and Web of Science were searched up to August 2021 to identify studies reporting the diagnostic performance of WB-MRI for the assessment of hematological malignancies’ treatment response. A bivariate random-effects model was applied for the generation of the pooled diagnostic performance. Results Fourteen studies with 457 patients with lymphoma, multiple myeloma, and sarcoma (very small proportion) were analyzed. Overall pooled sensitivity and specificity of WB-MRI were 0.88 (95% CI: 0.73–0.95) and 0.86 (95% CI: 0.73–0.93), respectively. Studies using whole-body diffusion-weighted imaging (WB-DWI) showed higher sensitivity than those that did not (0.94 vs. 0.55, p = 0.02). The pooled concordance rate of WB-MRI to assess hematological malignancies’ treatment response with reference standard was 0.78 (95% CI: 0.59–0.96). WB-MRI and PET/CT showed similar diagnostic performance (sensitivity [0.83 vs. 0.92, p = 0.11] and specificity [0.87 vs. 0.76, p = 0.73]). Conclusion WB-MRI has high diagnostic performance for hematological malignancies’ treatment response assessment. The adding of WB-DWI is strongly associated with increased sensitivity.